Two Siblings With Valproate-Related Hyperammonemia and Novel Mutations in Glutamine Synthetase (GLUL) Treated With Carglumic Acid - Bennett, Jennifer (Child Neurol Open, 2020)
This case report describes 2 siblings with myoclonic epilepsy who had novel mutations in the glutamine synthetase (GLUL) gene: c.316C>T, p.(Arg106*) and c.42G>C, p.(Lys14Asn). Valproic acid improved seizure control, but was associated with hyperammonemic encephalopathy. Addition of carglumic acid reduced ammonia levels but drug coverage was declined. We therefore designed a protocol to measure the reduction in plasma ammonia in response to carglumic acid therapy. After the first dose of carglumic acid, Patient 1 showed a reduction in plasma ammonia levels within 3 hours, from 114 umol/L to 68 umol/L (reference 12-47 umol/L), and Patient 2 from 108 umol/L to 80 umol/L, which was sustained over a 2 week period. Overall, there was a strong negative correlation between plasma ammonia levels and carglumic acid levels (r = −0.86, p = 0.0013), and recurrence of hyperammonemic encephalopathy was not observed while the patients were taking carglumic acid.